The group refractive indices of HF waves in the ionosphere and departure from the magnitude without collisions - Aydogdu, M; Yesil, A; Güzel, E (Pergamon-Elsevier Science Ltd, 2004)
We arc interested in the group refractive indices of high-frequency waves propagating in the collisional ionosphere. New functions have been added to the formulas of the group refractive indices for the case when collisions are absent. Applications to the ionosphere show that the departures of the group refractive index from the magnitude without collisions is proportional to Z(2) when X < 1, and proportional to Z when X > 1. Maximum effect of the collisions the group refractive index is obtained around reflection points. (C) 2004 Elsevier Ltd. All rights reserved.
Keywords: The group refractive index; effects of collisions; HF waves; ionosphere